Performance assessment of conveyor oven system on proportional integral derivative and programmable logic controller base fuzzy logic controller - Yeoh, Kok Wei (2022)
In the industrial conveyor oven system, temperature stability and uniformity are important factors that need to be precisely controlled by temperature controller. Therefore, an existing industrial conveyor oven system for springs manufacturing industry is selected to perform the assessment of the temperature controlled by PID temperature controller and fuzzy logic system. In this project, real time temperature data of various type of springs that undergone heat treatment process at the oven is collected for analysis. The control of the oven is initially by PID temperature controller and then replaced with MATLAB simulink fuzzy logic model with PLC, the outcome of both system is analyze based on the temperature stability according to temperature setpoint defined by operator. Other than that, it is involved analyzing the heater current consumption, electro-mechanical contactor internal structure, and solid-state relay performance. All the collective data is analyzed, and modification is made based on the result outcome. In addition, the test run result of using matlab simulink fuzzy logic and PID temperature controller to control the oven temperature, it is found out that different temperature setpoint and different temperature monitoring location require different range of duty cycle for the solid-state relay operation as to maintain the temperature in the oven chamber accordingly to setpoint. Result of this study shows that PID temperature controller for the oven system control can maintain the oven temperature accordingly to different setpoint and no additional hardware is required.